Small Interfering RNA in Kidney Diseases: Promises and Limitations - Attilio Losito; Giuseppe Solano (Kidney and Dialysis)
Small interfering RNAs (siRNAs) are short, double-stranded RNA molecules that play a crucial role in the regulation of gene expression, particularly through a natural process called RNA interference (RNAi). Their discovery, about 25 years ago, paved the way for a whole series of research leading to synthetic molecules. The gene silencing potential of these siRNAs was initially oriented towards diseases resulting from genetic dysfunctions. This led to the development of the first synthetic siRNAs approved for human use in hereditary transthyretin amyloidosis. Subsequently, the field of application expanded beyond the confines of genetic diseases. The refinement of pharmacological techniques has led to the synthesis of a variety of siRNAs capable of blocking the production of individual proteins responsible for various disease conditions, thus expanding their field of therapeutic application. The kidney has also been affected by this new therapeutic tool, largely indirectly but also, with some difficulty, directly. The structural complexity of the kidney has made the search for siRNAs targeting its individual components very challenging. Nevertheless, the first results of the application of this new therapeutic technology to the kidney are beginning to be seen in experimental animals and in humans. siRNAs have been approved for the treatment of amyloidosis with patisiran and oxalosis with lumasiran and nedosiran. Studies are ongoing for the use of siRNAs as anti-complement drugs in IgA nephropathy, as angiotensinogen inhibitors in hypertension, or against some mediators of acute kidney injury. In this review, the biological mechanisms underlying the use of siRNAs are briefly exposed. The results of the therapeutic application of RNA interference to the kidney and its diseases are also analyzed and discussed.